2021
DOI: 10.1149/1945-7111/abdde7
|View full text |Cite
|
Sign up to set email alerts
|

Application of Gas Chromatography Hyphenated to Atmospheric Pressure Chemical Ionization-Quadrupole-Time-of-Flight-Mass Spectrometry (GC-APCI-Q-TOF-MS) for Structure Elucidation of Degradation Products Based on the Cation in Pyr14TFSI

Abstract: In this study, the hyphenation of gas chromatography to atmospheric pressure chemical ionization-quadrupole-time-of-flight-mass spectrometry (GC-APCI-Q-TOF-MS) is applied for the investigation of degradation products of ionic liquid (IL) based electrolytes. The advantage of APCI compared to electron ionization (EI) for amine-based analytes due to a higher sensitivity of the molecular ion was demonstrated and the results obtained in this work contribute to a better understanding of the IL aging behavior in rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 63 publications
1
2
0
Order By: Relevance
“…The according Hofmann-elimination product of the N 1114 + cation, trimethylamine, was detected at earlier retention times t r due to its high volatility, as depicted in Figure S5 in the Supporting Information. Interestingly, also reaction products from intramolecular Hofmann-eliminations (Ic, IIc, and IIIc), as described for Pyr 14 TFSI in the literature, [29,34] could be detected for Pyr 14 TFSI, but also for Pyr 13 TFSI and Pip 14 TFSI. This type of ring-opening reaction is plausible, as the pyrrolidinium and piperidinium rings of the IL cations presumably are prone to deprotonation in β-position.…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…The according Hofmann-elimination product of the N 1114 + cation, trimethylamine, was detected at earlier retention times t r due to its high volatility, as depicted in Figure S5 in the Supporting Information. Interestingly, also reaction products from intramolecular Hofmann-eliminations (Ic, IIc, and IIIc), as described for Pyr 14 TFSI in the literature, [29,34] could be detected for Pyr 14 TFSI, but also for Pyr 13 TFSI and Pip 14 TFSI. This type of ring-opening reaction is plausible, as the pyrrolidinium and piperidinium rings of the IL cations presumably are prone to deprotonation in β-position.…”
Section: Resultssupporting
confidence: 61%
“…As the peak intensity dependent of the amount of degradation products, it can be concluded that the extent of galvanic corrosion of Li is heavily dependent on the concentration of LiTFSI in the IL-based electrolyte. A correlation between degradation stability and LiTFSI content was reported in the literature only for Pyr 14 TFSI, [34] but the reactivity of Pyr 13 TFSI, Pip 14 TFSI, and N 1114 TFSI appears to follow a similar pattern. During galvanic corrosion, electrons from the Li pass through the metal of higher electrochemical potential and enable reactions at the metal-electrolyte interface.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Another interesting observation is the gradual lowering of the binding energy of the N 1s peak assigned to PYR 13 with increasing cycle number. References indicate decomposition reactions for PYR 13 that give rise to an organic SEI layer. This observation of the gradual decomposition of PYR 13 may also be linked to the high amount of CB peak seen for cathodes cycled in the co-solvent electrolyte, in a way that the CB peak has overlapping signals originating from PYR 13 decomposition products at the anodes.…”
Section: Resultsmentioning
confidence: 99%